Colchicine – from Gout to Covid-19 - Ekadana Prayoga Suryadi; Keith Justine Thiotansen; Reynaldi Hardianto Saputra; Priscilla Angeline; Novia Yolanda (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Colchicine is a toxic and carcinogenic alkaloid obtained from the plant extract Colchium autumnale and has been used to treat arthritis (gout) for centuries. The results of clinical trials show that low-dose colchicine is effective for the management of acute gout as well as for long-term maintenance profiling (53) and the use of colchicine is known to reduce the symptoms of inflammatory responses related to COVID-19 and reduce the frequency of other manifestations such as pulmonary infiltrates, headaches and arthralgia. However, so far studies have shown that colchicine is not used as an initial or primary treatment to treat COVID-19 but as a treatment that is